From azada to trillo: The nouns designating agricultural tools in the COSER and the CORPES XXI. Lexicographic Implications - González Cobas, Jacinto (2021)
Experts agree that there have been significant changes in the way dictionaries are planned and produced. One of them is the search for channels from which the collaboration between theoretical linguistics and lexicography can be intensified; nevertheless, the formulae needed to prevent such postulate from being a mere statement of intent are not always adequately fixed. Corpora are tools which enable that relationship, and they are a reference for the establishment of definition models applicable to homogeneous groups of words, in our case, the nouns designating agricultural tools, which have received a very heterogeneous lexicographic treatment in the last edition of the Diccionario de la lengua española (DLE) by RAE.